Plan para la mejora en la gestión de los procesos de programación, elaboración de presupuesto, control y calidad de obra en la Empresa D’QS S.A.S. de Medellín, Colombia - Montenegro-Méndez, Marcos Antonio (Instituto Tecnológico de Costa Rica, 2017)
The developed work consists in the intervention of four constructive process from the company D’QS S.A.S. in Medellín, Colombia. The objective is to develop an integral plan for improve the management of the processes of programming, budget preparation, control and quality on site, for which are applied documental reviews, SWOT analysis, surveys, the current structures are modified and adapted, and they are new mechanisms incorporated. As a result of the directed actions, four improved tools are obtained with standardized work formats and integrated between each other. The implementation strategy consists of six phases that allow the incorporation of new tools and enhance the actions of the company for its growth. Among the main conclusions is that the SWOT analysis shows qualities such as knowledge, experience, dynamism and initiative for the growth of the company, the intervened processes now have new tools to manage projects with up to 340 tasks, and the implementation strategy requires the investment of approximately 17 months including the actions that enhance the company's growth.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Planes; Gestión; Presupuesto; Proyectos; Control; Costos; Calidad; Estrategia